The Role of Sharia in Constitutional Systems: A Comparative Study of Indonesia and Malaysia - Arinal Arinal; Yeni Widowaty (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
The integration of Sharia into constitutional systems has become a significant issue in modern Muslim-majority states seeking to balance Islamic values with the principles of the rule of law, democracy, and human rights. Previous studies have examined the implementation of Sharia in specific areas, such as family law, Islamic finance, and religious institutions. However, there remains limited comparative research on the constitutional position, legal integration, and institutionalization of Sharia within the state systems of Indonesia and Malaysia, particularly concerning the formulation of an ideal constitutional model for modern governance. This study aims to analyze the role and position of Sharia within the constitutional systems of both countries, compare their models of legal and institutional integration, and formulate an ideal model for the integration of Sharia. This normative legal research employs statutory, conceptual, and comparative approaches. The findings reveal that Indonesia adopts a pluralistic-substantive model in which Sharia is accommodated through legislation and state institutions without explicit constitutional recognition. In contrast, Malaysia adopts a formal-institutional model supported by a dual legal system that grants Sharia a stronger constitutional and institutional status. This study proposes a constitutional-progressive model that harmonizes Sharia values with constitutional supremacy, democracy, the rule of law, and the protection of human rights.